2022
DOI: 10.1155/2022/3163230
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Meta‐Analysis of the Effect of Dietary Care on Nausea and Vomiting in Oncology Chemotherapy Patients

Abstract: Objective. To evaluate the effect of dietary care on chemotherapy-induced nausea and vomiting in oncology patients. Methods. A retrospective analysis of digestive symptoms was conducted in cancer patients admitted to our hospital, who received chemotherapy, and corresponding effective dietary care countermeasures were adopted. Results. After the nursing intervention, the incidence of digestive symptoms was significantly reduced, the quality of life was significantly improved (59.92 ± 6.57) vs. (37.95 ± 7.50), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%